2019
DOI: 10.7554/elife.51114
|View full text |Cite
|
Sign up to set email alerts
|

Straightjacket/α2δ3 deregulation is associated with cardiac conduction defects in myotonic dystrophy type 1

Abstract: Cardiac conduction defects decrease life expectancy in myotonic dystrophy type 1 (DM1), a CTG repeat disorder involving misbalance between two RNA binding factors, MBNL1 and CELF1. However, how DM1 condition translates into conduction disorders remains poorly understood. Here we simulated MBNL1 and CELF1 misbalance in the Drosophila heart and performed TU-tagging-based RNAseq of cardiac cells. We detected deregulations of several genes controlling cellular calcium levels, including increased expression of stra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 54 publications
(76 reference statements)
2
22
0
Order By: Relevance
“…The overexpression alone of this subunit in the Drosophila was sufficient to reproduce asynchronous heartbeats. In addition, this Ca V 1.2 subunit was also found elevated in hearts from DM1 patient with conduction defects 45 . These results support ours and suggest a predominant role of calcium channels in cardiac electrical abnormalities in DM1 patients.…”
Section: Discussionmentioning
confidence: 83%
“…The overexpression alone of this subunit in the Drosophila was sufficient to reproduce asynchronous heartbeats. In addition, this Ca V 1.2 subunit was also found elevated in hearts from DM1 patient with conduction defects 45 . These results support ours and suggest a predominant role of calcium channels in cardiac electrical abnormalities in DM1 patients.…”
Section: Discussionmentioning
confidence: 83%
“…Briefly, this technique allows the analysis and quantification of rhythmicity and the dynamics of the heart contractions, including the relaxation phase (DI, diastolic interval), contraction phase (SI, systolic interval), heart period (HP), arrhythmia index (AI), end systolic diameter (ESD), end diastolic diameter (EDD), and the percentage of fractional shortening (Figure 2A). Recent work by our group [76] revealed that heart-specific DM1 models showed the asynchronous propagation of cardiac contraction waves mimicking the conduction defects observed in DM1 patients. To identify genes involved in DM1-associated conduction disturbances, transcripts were isolated specifically from the DM1 fly hearts using a TU-tagging approach, followed by RNA sequencing [76].…”
Section: Modeling Myotonic Dystrophy Type 1 Heart Defectsmentioning
confidence: 90%
“…Recent work by our group [76] revealed that heart-specific DM1 models showed the asynchronous propagation of cardiac contraction waves mimicking the conduction defects observed in DM1 patients. To identify genes involved in DM1-associated conduction disturbances, transcripts were isolated specifically from the DM1 fly hearts using a TU-tagging approach, followed by RNA sequencing [76]. This showed that the expression of straightjacket (stj)/Calcium Voltage-Gated Channel Auxiliary Subunit Alpha 2 delta 3 (CACNA2D3)/α2δ3), involved in heart contraction, was significantly increased in the cardiac cells of DM1 flies [76].…”
Section: Modeling Myotonic Dystrophy Type 1 Heart Defectsmentioning
confidence: 90%
See 1 more Smart Citation
“…The fruit flies were used to test candidate small molecules such as pentamidine and daunorubicin which disrupt MBNL1 binding to (CUG) repeats, and which were shown to have beneficial effects in these models. Another group has used cardiac specific depletion of MBNL1 (Mbl) or overexpression of CELF1 (Bruno-3) in Drosophila to model cardiac conduction defects, and to identify potential new targets such as CACNA2D3 (a regulatory subunit of Ca-α1D/Ca v 1.2 voltage gated calcium channel) [ 109 ]. As with the cell-based assays, these studies show the potential of these models to study mechanisms of RNA toxicity, and in drug screens designed to identify therapies for DM1.…”
Section: Cell and Drosophila Model Systems For Studying Cardiac Rna Toxicity In Dm1mentioning
confidence: 99%